Reviews (New blackfriars, 1967)
WILLIAM GOLDING: A CRITICAL STUDY, by Mark Kinkead-Weekes and Ian Gregor. THE WARES OF AUTOLYCUS. Selected Literary Essays of Alice Meynell, Chosen and introduced THE EXPLORING WORD, by David Holbrook. Cambridge University Press ON THE INSPIRATION OF SCRIPTURE, by John Henry Newman. Edited with an introduction by J. Derek Holmes and Robert Murray, S.J. WESLEYAN AND TRACTARIAN WORSHIP: An oecumenical study. By Trevor Dearing. THE WORSHIP OF THE REFORMED CHURCH, by John M. Barkley. (Ecumenical Studies in Worship No. 15.) BACKGROUND AND BELIEF, by R. J. Rees. SOCIAL HISTORY AND CHRISTIAN MISSION, by Max Warren. NEW MEANINGS IN HISTORY, by Alban G. Widgery. IN SEARCH OF PHILOSOPHIC UNDERSTANDING, by E. A. Burtt. SEEING, KNOWING AND BELIEVING, by J. F. Soltis. INTERNATIONAL COMMITTEE ON ENGLISH IN THE MASS: English for the Mass, Part II. 1967. NEW DICTIONARY OF THE LITURGY, by Gerhard Podradsky. Edited in English by Lancelot Sheppard. A READER IN CONTEMPORARY THEOLOGY, ed. by John Bowden and James Richmond, London. THE INFERTILE PERIOD, by J. Marshall. Helicon Press, Baltimore.